A π‐Conjugated Anion‐Exchange Membrane with an Ordered Ion‐Conducting Channel via the McMurray Coupling Reaction. Issue 4 (14th December 2022) - Zhang, Fan; Zhang, Yang; Sun, Lixuan; Wei, Chengpeng; Zhang, Huaqing; Wu, Liang; Ge, Xiaolin; Xu, Tongwen
Abstract: The McMurry coupling is a facile, gentle and low‐cost chemical reaction for synthesizing. Here, for the first time, we employed the McMurry coupling reaction to prepare π‐conjugated anion exchange membranes (AEMs). The inter‐chain π‐π stacking between adjacent benzene rings induces directional self‐assembly aggregation and enables highly ordered ion‐conductive channels. The resulting structure was characterized through UV/VIS spectrum, X‐ray diffraction (XRD) pattern, small‐angle X‐ray scattering (SAXS), transmission electron microscopy (TEM) and density functional theory (DFT) calculations, leading to high OH − conductivity of 135.5 mS cm −1 at 80 °C. Furthermore, the double bonds in the π‐conjugated system also trigger in situ self‐crosslinking of the AEMs to enhance dimensional and alkaline stability. Benefiting from this advantage, the as‐obtained Cr‐QPPV‐2.51 AEM exhibits superior alkaline stability (95 % conductivity retention after 3000 hrs in 1 M KOH at 80 °C) and high mechanical strength of 34.8 MPa. Moreover, the fuel cell using Cr‐QPPV‐2.51 shows a maximum peak power density of 1.27 W cm −2 at 80 °C. Abstract : McMurry coupling was used to prepare π‐conjugated anion exchange membranes (AEMs). The inter‐chain π‐π stacking between adjacent benzene rings induces directional self‐assembly aggregation and enables highly ordered ion‐conductive channels, leading to a high OH − conductivity of 135.5 mS cm −1 at 80 °C. The double bonds in the π‐conjugated system trigger in situ self‐crosslinking of the AEMs to enhance dimensional and alkaline stability.